2019
DOI: 10.3389/fimmu.2019.01621
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Promotes Myocardial Remodeling During Diet-Induced Obesity

Abstract: Background: Obesity is an increasingly prevalent metabolic disorder in the modern world and is associated with structural and functional changes in the heart. The NLRP3 inflammasome is an innate immune sensor that can be activated in response to endogenous danger signals and triggers activation of interleukin (IL)-1β and IL-18. Increasing evidence points to the involvement of the NLRP3 inflammasome in obesity-induced inflammation and insulin resistance, and we hypothesized that it also could play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…In the present study, we observed that the NLRP3 inflammosame, which plays an important role in the development of obesityrelated cardiac dysfunction and remodeling (Sokolova et al, 2019), was either absent or only very weakly expressed in the cardiomyocytes of lean mice (Figure 4A), whereas ob/ob mice showed moderate expression of this pro-inflammatory marker in the cytoplasm of cardiomyocytes (Figure 4B). Interestingly, NLRP3 was significantly suppressed (absent/very weak expression) in ob/ob mice supplemented with melatonin ( Figure 4C).…”
Section: Heart Inflammation Evaluationmentioning
confidence: 60%
“…In the present study, we observed that the NLRP3 inflammosame, which plays an important role in the development of obesityrelated cardiac dysfunction and remodeling (Sokolova et al, 2019), was either absent or only very weakly expressed in the cardiomyocytes of lean mice (Figure 4A), whereas ob/ob mice showed moderate expression of this pro-inflammatory marker in the cytoplasm of cardiomyocytes (Figure 4B). Interestingly, NLRP3 was significantly suppressed (absent/very weak expression) in ob/ob mice supplemented with melatonin ( Figure 4C).…”
Section: Heart Inflammation Evaluationmentioning
confidence: 60%
“…Furthermore, a reduction in the secretion of insulin-sensitive adipokines accompanied by oversecretion of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) is closely related to the etiology of various metabolic conditions. Other studies also point to the participation of NLRP3 in obesity because of its overexpression in AT [11,[69][70][71][72][73]. Moreover, the results of studies on mouse models of obesity are consistent with this observation [74,75].…”
Section: Obesity and T2dsupporting
confidence: 59%
“…However, when investigated in the LV tissue, IHC revealed no difference in the levels of ceramide between the genotypes. We have previously described the lack of both myocardial inflammation and fibrosis in our model of NLRP3 deficiency on HFD 22 compared to others 44,45 , and it is tempting to hypothesize that this at least partly could be due to differences in cardiac ceramide accumulation. Thus, whereas our findings support a link between NLRP3-driven inflammation and ceramide signaling systemically, the role of these pathways within the myocardium could be questioned.…”
Section: Discussionmentioning
confidence: 62%